Perinatal depression screening and prevention: Descriptive findings from a multicentric program in the South of Italy - Bellomo, Antonello; Severo, Melania; Petito, Annamaria; Nappi, Luigi; Iuso, Salvatore; Altamura, Mario; Marconcini, Alessia; Giannaccari, Elisa; Maruotti, Giuseppe; Palma, Giuseppe Luigi; Vicino, Mario; Perrone, Antonio; et al. (Frontiers in Psychiatry, 2022)
Introduction: Perinatal Depression (PD) is a cluster of clinical depressive symptoms occurring during pregnancy or after the childbirth with a prevalence of 11.9%, globally. Risk factors for PD among pregnant women may include personality trait of neuroticism, low personal resilience, higher anxiety and avoidance in the close relationships as well as dysfunctional coping strategies. Methods: we report on descriptive findings of a screening/prevention program aimed to detect depressive symptoms and associated risk factors in a large sample of women (N=1664) accessing the gynecological departments of the Regione Puglia (South of Italy) from July to November 2020. Pregnant women were assessed at their third trimester of pregnancy (T0), after the childbirth (T1) and those at risk for PD within one year from the delivery (T2-T4); The Edinburgh Postnatal Depression Scale (EPDS) has been employed for the screening of PD over time as well as other standardized measures for neuroticism, resilience, coping strategies and quality of life. Results: Of 1664, n=1541 were tested at T1 and 131 scored≥12 at EPDS (14.6±2.95) showing a higher risk for PD. They were followed over time at 1, 6 and 12 months after the childbirth (T2-T4) and 15 of them scored≥ 12 (EPDS) at T4. Women with higher risk of PD also reported higher levels of neuroticism, lower levels of personal resilience, more anxiety and avoidance in close relationships as well as higher employment of dysfunctional coping strategies (e.g. denial, self-blame, etc.) and lower quality of life (0.0008< all p<0.0001). Conclusions: this study confirmed the benefit of screening programs for the early detection of PD among pregnant women. We may suggest a set of risk factors to be considered in the clinical assessment of PD- risk as well as the promotion of similar programs in order to improve depressive outcomes and pathways to care for PD on the basis of a more accurate assessment and referral.